Law Reports of the Commonwealth: Criminal law reports (Professional Books AbingdonGB, 1985)
Contains cases dealing with general topics such as constitutional issues, jurisdiction, criminal procedure, criminal evidence, the appeal process, general principles of criminal liability, homicide, sentencing, inter alia. Cases are chronologically arranged and cover jurisdictions from several regions of the Commonwealth. Includes alphabetical list of cases reported, cases, constitutions, legislation and other sources referred to, and a subject-matter index.
Doc. Centre has: '85; '89; '90